Motivations for Punishing Someone Who Violates HIV Nondisclosure Laws: Basic Research and Policy Implications. Issue 1 (26th November 2014) - Woody, Alex; Braitman, Abby L.; Derlega, Valerian J.; Winstead, Barbara A.; Neilson, Brittany
Abstract : Many U.S. states have HIV nondisclosure laws that require HIV‐positive persons to disclose their HIV status to new sexual partners. Mandating HIV disclosure before sexual activity occurs is intended to deter unsafe sexual behavior and to reduce the risk of HIV transmission. HIV nondisclosure laws are also intended to punish HIV‐positive persons who violate these laws. Vignettes were used to examine if participants are motivated to punish someone who violates these HIV nondisclosure laws. In three studies, we found that retribution but not general deterrence was used to recommend punishment, especially when HIV nondisclosure was associated with harm being done to sexual partners. We also found that preventing the law violator from reoffending played a role in recommending punishment, especially if the law violation was associated with considerable harm. On the other hand, the expression of an apology to sexual partners was associated with less severe punishment, based on the assessment that there was a relatively low risk of the HIV law violator repeating this crime and, therefore, lower importance for removing him from society. The findings suggest that persuading the general public and legislators to end the criminalization of HIV nondisclosure will be an uphill battle.